Rethinking Holocaust justice : essays across disciplines - Goda, Norman J. W. 1961- HerausgeberIn (Berghahn Books, 2018)
Before the law : the poetics of justice in Eichmann in Jerusalem / Eric Kligerman -- Criminal trials as rituals of purification / Katharina von Kellenbach -- What kind of narrative is legal testimony? : Terezín witnesses before Czechoslovak, Austrian, and German courts / Anna Hájková -- A morality of evil : Nazi ethics and the defense strategies of German perpetrators / Kerstin von Lingen -- The "second wave" of Soviet justice : the 1960s war crimes trials / Alexander V. Prusin -- "Not quite Klaus Barbie, but in that category" / Mykola Lebed -- The CIA, and the airbrushing of the past / Per Anders Rudling -- Convicting the cog : the Munich trial of John Demjanjuk / Lawrence Douglas -- Reparations, victims, and trauma in the wake of the holocaust / Regula Ludi -- Achieving a measure of justice and writing holocaust history through American restitution litigation / Michael J. Bazyler -- The fortunate possessor : the case of Gustav Klimt's Beethoven frieze / Sophie Lillie -- Judging from without : public pressure and postwar justice / JonDavid K. Wyneken -- Rough justice and the American approach to war crimes prosecution : Dachau, Guantanamo Bay, and the Nuremberg exception / Tomaz Jardim